Why are major accidents still occurring?. Issue 3 (14th November 2015) - Silva, Elisio Carvalho
Abstract : The loss of technological knowledge is an important contributing factor to a major accident occurs. This article analyzed several major accident reports to corroborate to this premise. The more an organization moves further away from a known technology, the risk of an accident occurring considerably increases. This work discusses three ways in which technological knowledge can be lost: (1) new technology; (2) loss of knowledge due to inadequate training, procedures, and information; and (3) the failure to incorporate new knowledge (e.g., the lessons learned). For each means of technological knowledge loss, this article refers to an important major accident and shows how it contributed to the accident. It also addresses the types of failures and the concept of independent protection layers to help explain how to reduce the possibility of a major accident occurs. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 253–257, 2016